1999
DOI: 10.1046/j.1365-2036.1999.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of colonic detoxication enzyme activity in mice with dextran sulphate sodium‐induced colitis

Abstract: Background : The increased risk of colonic malignancies in individuals with ulcerative colitis has prompted a search for early biomarkers of disease progression. Aim : To characterize Phase II detoxication enzyme expression during acute and chronic colitis. The mouse model of dextran sulphate sodium (DSS)‐induced colitis represents a relevant system with which to sequentially evaluate the spectrum of biochemical changes associated with colorectal cancer risk. Methods : Acute and chronic colitis were induced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…It is unclear whether the relationship of IL-1␤ tissue levels and the degree of mucosal inflammation and necrosis during IBD can be attributed to lack of GST-mediated defense since correlative studies have not yet been performed. However, studies of colonic mucosal antioxidant enzymes in patients with IBD and in animal models of colitis have revealed significant reductions in total glutathione S-transferase activity (Bhaskar et al, 1995;Clapper et al, 1999) and superoxide dismutase activity (Lih-Brody et al, 1996), indicating that antioxidant defenses are compromised during colitis.…”
Section: Downloaded Frommentioning
confidence: 99%
“…It is unclear whether the relationship of IL-1␤ tissue levels and the degree of mucosal inflammation and necrosis during IBD can be attributed to lack of GST-mediated defense since correlative studies have not yet been performed. However, studies of colonic mucosal antioxidant enzymes in patients with IBD and in animal models of colitis have revealed significant reductions in total glutathione S-transferase activity (Bhaskar et al, 1995;Clapper et al, 1999) and superoxide dismutase activity (Lih-Brody et al, 1996), indicating that antioxidant defenses are compromised during colitis.…”
Section: Downloaded Frommentioning
confidence: 99%
“…A chronic colitis could be induced by feeding 30-50 g/L DSS in drinking water for 7 d followed by 7-14 d of water [6,[8][9][10] . In recent years, some researchers have described the occurrence of dysplasia and/or cancers in mice when they are subjected to repeated administration of DSS in a long term [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…The staining level of mGST A4-4 increased after DSS administration and induction of colitis in the conventional mice. This finding may appear surprising, since it has previously been reported that GSTs were downregulated in mice with DSS-induced colitis (Clapper et al 1999) and that GST alpha could not be detected. However, GST A4-4 is the structurally most distant member of the alpha class and has minimal immunological crossreactivity with other class members.…”
Section: Discussionmentioning
confidence: 52%
“…One experimental model, the dextran sulfate sodium (DSS)-induced colitis, presented in 1990 (Okayasu et al 1990), has now been adopted as a relevant model for the study of human inflammatory bowel disease (IBD), inflammatory mechanisms, and therapy (Grisham 1993;Elson et al 1995;Axelsson et al 1996Axelsson et al , 1998Axelsson 1999;Spiik et al 2002). The administration of DSS, and other sulfated polysaccharides, also induces the development of cancer (Ishioka et al 1987;Yamada et al 1992Yamada et al , 1993Cooper et al 2000), which has been attributed to ineffective or deficient detoxication of xenobiotics (Clapper et al 1999).…”
Section: Introductionmentioning
confidence: 99%